Factores que influyen en la interacción humana del cuidado de Enfermería (2006)
ABSTRACT: Human relationships involved in the nursing care practice are related with several conditions whose knowledge may influence the contact among nurses and patients in order to cause expected results such as to cope with illness, promote healing and die with dignity. The kind of interactions, the role of nurses, the stages of the interactions and some other conditions related to patients during the interactions have been identified and analyzed by some nursing theorist. The human interaction allows to define the nursing and it is the way to carry out the care. It is for this reason that should be analyzed and re taken with each step that the nursing discipline advances. This is a bibliographic revision article based on thoughts of theorist in nursing and dispositions of the ethic in nursing law about nurse – patient interactions.